Are All ESG Funds Created Equal? Only Some Funds Are Committed - Lowry, Michelle; Wang, Pingle; Wei, Kelsey D (Review of Financial Studies, 2026)
Abstract Environmental, social, and governance (ESG) funds have heterogeneous incentives to engage with portfolio firms. If funds view ESG as a value driver, then these incentives will affect funds’ behavior and thus their impact on firms. We compare ESG funds with similar levels of ESG investments but different incentives to engage. Funds with higher incentives to engage, that is, committed ESG funds, conduct more ESG-related information acquisition, pursue longer term investment strategies, engage more intensely on ESG issues, and have greater real impacts. Moreover, committed ESG funds have outperformed other ESG funds within subportfolios with higher and more effective ESG engagement.